VELOCITY OF P WAVES IN THE EARTH'S CORE: NEW RESULTS - Burmin V.Yu. (My University, 2003)
Based on the record part of seismic oscillation records of deep-focus earthquakes registered by the global network, traveltime curves were constructed for refracted and reflected short-period seismic P waves propagating in the Earth's core. Based on these traveltime curves, we constructed a velocity part of the core that agreed well with the observed data and explained the nature of precursors, i.e., oscillations registered on the Earth's surface during the first arrival at an epicentral distance of 134°-142°. The velocity part of the outer core has the following specific feature. Its lower part includes a layer about 500 km thick with a high velocity gradient. This layer is underlain by another ∼200-km-thick layer with a decreased velocity (F zone). In the inner core, the velocity at first rather strongly increases to a depth of approximately 5500 km and then changes practically linearly toward the Earth's center with a slightly higher gradient than accepted in standard models.